2007
DOI: 10.1111/j.1749-7345.2007.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Cellular Component in Inflammatory Response Induced by Different Stimuli in the Swim Bladder of Pacu, Piaractus mesopotamicus Holmberg 1887 (Characidae)

Abstract: Abstract.-The present study assessed the kinetics of cell accumulation at the site of inflammation induced by thioglycolate, Escherichia coli lipopolysaccharide (LPS) and heat-inactivated Aeromonas hydrophila, in the pacu, Piaractus mesopotamicus (Characidae), swim bladder. A quantitative, as well as qualitative, assessment was done of all the cells present in the exudate at 6, 24, and 48 h (n 5 8) after inoculation of inflammatory agents. The results show that the thioglycolate was the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
9

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 17 publications
(25 reference statements)
3
24
1
9
Order By: Relevance
“…In fact, whether thrombocytes are involved in fish cell response, these results could suggest their participation in such event. This is especially true in analyzing the findings with tilapia inflammation (Martins et al, 2004b;Bozzo et al, 2007). In this previous study, thrombocytes were the main cells present in the inflammatory exsudate suggesting their importance in fish cell response.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In fact, whether thrombocytes are involved in fish cell response, these results could suggest their participation in such event. This is especially true in analyzing the findings with tilapia inflammation (Martins et al, 2004b;Bozzo et al, 2007). In this previous study, thrombocytes were the main cells present in the inflammatory exsudate suggesting their importance in fish cell response.…”
Section: Discussionmentioning
confidence: 79%
“…It must be commented that the injection in the swim bladder could not be as aggressive to the same degree of intraperitoneal injection. Previous study showed the security in the use of the swim bladder as an inflammatory site (Martins et al, 2004a, Bozzo et al, 2007 by dint of the fact that this organ suffers little influence of contamination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, the assessment of inflammatory response depends on three major factors: first is the difficulty of identification of leukocytes, that depends on the species, the second is related to ontogenetic variation in blood and inflammatory cells (Tavares- Dias and Moraes, 2004), and third kinetics of inflammatory process, which may be influenced by dietary supplementation (Moraes et al, 2003;Belo et al, 2005Belo et al, , 2012Dotta et al, 2011), by the kind of inflammatory stimulous (Bozzo et al, 2007), by eicosanoids (Claudiano, 2011), by the ambiental temperature (Dias and Sinhorini, 1991;Jansson Junior and Waaler, 1967) and by circulating hormones (Martins et al, 2000;Belo et al, 2005Belo et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In fish, carrageenin, thioglycolate and inactivated Aeromonas hydrophila were tested in the swim bladder of Piaractus mesopotamicus (Martins et al, 2000;Moraes et al, 2003;Bozzo et al, 2007) and Oreochromis niloticus (Martins et al, 2004;Dotta et al, 2011). According to Bozzo et al (2007), thioglycolate and inactivated Aeromonas hydrophila induced vascular congestion, accumulation of thrombocytes followed by macrophages, granulocytes and oedema. The choice of swim bladder as local for assessment of inflammatory response is based on studies of Van Furth (1992), which showed that body cavities are an experimental model to represent the mechanisms of inflammatory response that can occur in the other animal tissues.…”
Section: Introductionmentioning
confidence: 99%